Controllable laser thermal cleavage of sapphire wafers. (March 2018) - Xu, Jiayu; Hu, Hong; Zhuang, Changhui; Ma, Guodong; Han, Junlong; Lei, Yulin
Highlights: In this paper, we studied the effects of laser processing on the quality of the machined wafer surfaces under different water cooling conditions. We first conducted finite element simulations to analyze the temperature and stress distribution under different investigated cooling conditions and different laser shapes. A wide depth ratio under multiple laser ablation passes was found to result in a substrate suitable for further processing. The surface after thermal cleavage was smooth and without damage. The luminous efficiency was obviously increased compared to that achieved with a substrate prepared using stealth dicing. Abstract: Laser processing of substrates for light-emitting diodes (LEDs) offers advantages over other processing techniques and is therefore an active research area in both industrial and academic sectors. The processing of sapphire wafers is problematic because sapphire is a hard and brittle material. Semiconductor laser scribing processing suffers certain disadvantages that have yet to be overcome, thereby necessitating further investigation. In this work, a platform for controllable laser thermal cleavage was constructed. A sapphire LED wafer was modeled using the finite element method to simulate the thermal and stress distributions under different conditions. A guide groove cut by laser ablation before the cleavage process was observed to guide the crack extension and avoid deviation. The surface and cross section of sapphire wafers processed using controllable laser thermal cleavage were characterized by scanning electron microscopy and optical microscopy, and their morphology was compared to that of wafers processed using stealth dicing. The differences in luminous efficiency between substrates prepared using these two processing methods are explained.